Measurement of CO2 solubility in NaCl brine solutions at different temperatures and pressures using the potentiometric titration method - Mohammadian, E.; Hamidi, H.; Asadullah, M.; Azdarpour, A.; Motamedi, S.; Junin, R. (American Chemical Society, 2015)
The solubility of CO2 in brine is one of the trapping mechanisms by which the CO2 is sequestrated in aquifers. in this research, an unconventional method, called the potentiometric titration, was used to Obtain the solubility of CO2 in distilled water and NaCl brine, The solubility data for the low salinity range are scarce in the literature. Thus, in this research, the CO, solubility was obtained in NaCl brines of low salinity (0-15 000 ppm) at temperatures between 60 degrees C and 100 degrees C and pressures up to 25 MPa. Moreover, the salting-out effect was estimated using the Setchenov's constant as a measure of reduction in solubility when salt is added to the solution. The solubility points obtained by the potentiometric titration method demonstrated very good consistency with those obtained by the previous methods.